Drugs associated with drug-induced interstitial lung diseases - O. D. Ostroumova; A. I. Listratov; A. I. Kochetkov; D. A. Sychev (Izdatelstvo OKI, 2021)
Interstitial lesion is one of the causes of respiratory failure. Drugs are a modifiable etiological factor of lung damage. Medications most commonly associated with drug-induced interstitial lung disease include antineoplastic drugs, disease-modifying anti-rheumatic drugs and amiodarone. According to the latest literature data, the previously described link between anti-rheumatic drugs and interstitial lung diseases is very inconsistent. It may even be a protective effect of this group of drugs on the lung tissue. The relationship between statin use and interstitial lesions is also complex and not fully understood. It is necessary to carefully assess the appearance of respiratory tract complaints in patients taking statins as in other groups of patients. Prescription of additional diagnostic methods is necessary to close monitoring and prevention the toxic effect of these drugs. These actions, as well as the potential prescription of steroid therapy and change in the underlying disease treatment approaches, are an important factor in reducing the incidence of respiratory failure in the population.